Impact of Patient Frailty on Intensive Care Unit Outcomes after Coronary Artery Bypass Grafting - MAHMOOD, MUHAMMAD MOHSIN; CHEEMA, SALIK AHMED; MIKRANI, BENAZEER; JUMADIN, ANEELA; YASIR, MUHAMMAD; NIAZI, ATTAULLAH KHAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Preoperative evaluation of frailty has typically relied on subjective measures and has evolved towards objective, standardized scales and tests. Patient frailty is one of the most important predictors for postoperative outcome, including mortality and morbidity. We sought to investigate whether patient frailty influences intensive care unit (ICU) outcomes following coronary artery bypass grafting (CABG). Findings from this study may provide important clinical implications in regard to the potential role of individualized preoperative evaluations and interventions for frail patients recovering from CABG in the ICU. Methods: 100 patients scheduled for elective isolated CABG between November 2024 and April 2025 were recruited in this observational study. Participants were divided into frail (n=50) and non-frail (n=50) according to the Essential Frailty Toolset (EFT). Preoperative, Intraoperative and Postoperative data was collected including parameters of 30-day mortality, duration of ICU stay, time on mechanical ventilation and postoperative arrhythmia. Result: Frail patients had a longer ICU stay (median 3.5 days vs 2 days, p=0.002), duration of mechanical ventilation (18 hours vs 11 hours, p<0.001) and postoperative arrhythmia (40% vs 20%, p=0.03) rate compared to non-frail patients. Furthermore, 5 frail patients developed postoperative stroke and none in the non-frail group did (p=0.02). The 30-day mortality was more common in frail patients (14% vs 2%, p=0.03). Frail patients were more commonly associated with surgical site infection, delirium and reoperation for bleeding, but these were not statistically significant. Conclusion: Frailty is a strong marker of poor ICU outcomes after CABG, correlated with more morbidity and higher incidence of 30-days mortality. Frail patients develop more complications during postoperative recovery, resulting in longer ICU length of stay and higher mortality rate.